GEOCHEMICAL CONSEQUENCES OF MELT TRANSPORT IN 2-D: THE SENSITIVITY OF TRACE ELEMENTS TO MANTLE DYNAMICS - Spiegelman M. (My University, 1996)
Dynamic models are presented to investigate the consequences of melting and melt transport for stable trace element geochemistry in open systems. These models show that including explicit melt transport in 2-D adds non-trivial behaviour because melts and residues can travel and mix along very different trajectories. Calculations are presented for both equilibrium and disequilibrium transport, and passive and active mid-ocean ridge flows. These calculations demonstrate that trace elements are sensitive to mantle dynamics and can readily distinguish between different end-member flow fields. Passive, plate-driven flow with strong melt focusing produces enrichments of incompatible elements. Active small-scale solid convection within the partially molten region, however, can lead to extreme dilution of incompatible elements, suggesting that this form of convection may not be significant beneath normal ridges. These calculations provide additional predictions about across-axis trends of geochemical variability and estimate the variation in concentrations that can occur even for a constant source. Many of these results are not seen in geochemical models that neglect melt transport and we discuss how this new behaviour affects the inferences drawn from simpler models.
Keywords: MANTLE; MELTS; TRANSPORT; TRACE ELEMENTS; GEOCHEMISTRY; OPEN SYSTEMS